Development of a novel amplicon based whole-genome sequencing framework for improved surveillance of Toscana virus - Martina Brandolini; Ludovica Ingletto; Giorgio Dirani; Silvia Zannoli; Andreea Maria Lapusneanu; Massimiliano Guerra; Alessandra Mistral De Pascali; Davide Lelli; Francesco Defilippo; Antonio Lavazza; Mattia Calzolari; Michele Dottori; et al. (Communications Biology)
Abstract Toscana virus (TOSV), a Phlebovirus transmitted by sandflies, is a leading cause of aseptic meningitis in the Mediterranean region. Despite its clinical significance, underreporting and limited availability of complete genomic data hinder a thorough understanding of its genetic diversity and evolution. This study presents a novel amplicon-based whole-genome sequencing (WGS) method using Illumina library preparation kits and proprietary software to optimize workflows and enhance bioinformatic analyses. Primers targeting TOSV lineage A genomes were designed with PrimalScheme to generate 400 bp amplicons, incorporating degenerate bases to improve coverage. Library preparation utilized Illumina Microbial Amplicon Prep (iMAP) kits, followed by de novo assembly using BaseSpace DRAGEN Targeted Microbial software. The method’s sensitivity was tested on viral propagates at various RNA concentrations (104 to 10 copies/μL), demonstrating robust performance at concentrations above 102 copies/μL. Validation on high-titre viral propagates (n = 7), low-titre clinical samples (n = 15), and phlebotomine pools (n = 5) confirmed its reproducibility and ability to comprehensively cover coding regions. Cerebrospinal fluid samples yielded the most consistent results compared to urine and sandfly pools. This innovative WGS approach represents a significant advancement in TOSV genomic surveillance, enabling large-scale studies of its genetic diversity and evolutionary dynamics, which are critical for improving diagnostics and public health strategies.